Android Based Application of Bussines License at Department Of Industry and Trade In Jayapura City - Wattimena, Fegie Yoanti; Batlyakru, Lukas (Pandawan Sejahtera Indonesia, 2021)
Android Based Application of Bussines License at Department Of Industry and Trade In Jayapura City was built with the aim of making it easier for applicants to apply for SIUP online using cellphones and to improve public services at the Jayapura City Industry and Trade Office. The processing of a Trade Business Permit (SIUP) which has been done manually, which is submitted directly to the Jayapura City Office of Industry and Trade, can be done by accessing it via an Android phone. The research methods used are 1) Data collection methods are carried out through literature studies, interviews and documentation, 2) application development methods with communication stages, planning quickly, designing quickly, modeling and designing quickly, forming prototypes, software to users and feedback. Programming language used is PHP MYSQL and AppGeyser. The results of the design are in the form of an application that can process input data: applicant's personal data, company data, submission data, admin data, data confirmation, SIUP upload and the resulting output is SIUP data print, SIUP application number report.